2012
DOI: 10.1158/1078-0432.ccr-12-0704
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Irradiated Tumor Cells Pulsed with an Adjuvant That Stimulates NKT Cells Is an Effective Treatment for Glioma

Abstract: Purpose: The prognosis for patients with glioblastoma multiforme (GBM) remains extremely poor despite recent treatment advances. There is an urgent need to develop novel therapies for this disease.Experimental Design: We used the implantable GL261 murine glioma model to investigate the therapeutic potential of a vaccine consisting of intravenous injection of irradiated whole tumor cells pulsed with the immuno-adjuvant a-galactosylceramide (a-GalCer).Results: Vaccine treatment alone was highly effective in a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(93 citation statements)
references
References 57 publications
4
89
0
Order By: Relevance
“…28,29 In humans, high iNKT cell numbers or activation of iNKT cells through glycolipids correlates with an improved outcome in different types of cancer. [30][31][32][33][34] Recent retrospective clinical data strongly support the beneficial immunologic effects of donor iNKT cells in the setting of allogeneic HCT in humans. Chaidos et al 35 showed in a multivariate analysis that a higher graft iNKT cell dose was associated with a significantly lower risk of acute GVHD.…”
Section: Cd49bmentioning
confidence: 95%
“…28,29 In humans, high iNKT cell numbers or activation of iNKT cells through glycolipids correlates with an improved outcome in different types of cancer. [30][31][32][33][34] Recent retrospective clinical data strongly support the beneficial immunologic effects of donor iNKT cells in the setting of allogeneic HCT in humans. Chaidos et al 35 showed in a multivariate analysis that a higher graft iNKT cell dose was associated with a significantly lower risk of acute GVHD.…”
Section: Cd49bmentioning
confidence: 95%
“…To maximally harness such immunological cascades, we established an efficient system using cells bearing a cell-associated Ag along with the iNKT cell ligand, a-galactosylceramide (a-GalCer). For example, we used iNKT ligand-loaded, tumor-associated Ag (TAA)-expressing CD1d + tumor cells (tumor/Gal) (19)(20)(21) or allogeneic fibroblasts loaded with a-GalCer transfected with TAA mRNA (16,22).…”
mentioning
confidence: 99%
“…23,47,63 Although CD1d is weakly expressed on C1498 cells and has been identified in other acute leukemic cell lines, including AML-ETO9a, 23 EL4, and WEHI-3B (L.R.A, unpublished data, June 14, 2014), we have previously demonstrated that a CD1d-negative a-GalCer-pulsed glioma vaccine can provide protection against glioma challenge. 25 We have also shown that CD1d-deficient DCs can transfer a-GalCer to host resident CD1d-expressing antigenpresenting cells in vivo to induce potent invariant NKT-cell activation, which likely reflects transfer of a-GalCer embedded within membranes of the injected cells. 46 It is therefore not necessary for NKT cells to interact directly via CD1d on the cells of the vaccine to provide adjuvant activity.…”
Section: Discussionmentioning
confidence: 67%
“…21,22 The glycolipid a-galactosylceramide (a-GalCer) has recently been shown to be a useful adjuvant for whole tumor cell vaccination by eliciting stimulatory interactions between dendritic cells (DCs) and natural killer T (NKT) cells. [23][24][25][26] When DCs acquire cellular material from irradiated tumor cells that have been treated with a-GalCer, the protein content is presented as peptides via major histocompatibility complex (MHC) molecules to CD4 1 and CD8 1 T cells, whereas the a-GalCer is presented via the MHClike molecule CD1d to NKT cells. Interactions between DCs and NKT cells promote CD40 signaling, leading to DC activation, which increases the capacity of DCs to stimulate peptide-specific T cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation